(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To develop a model for predicting the efficacy of treating DR in type 2 diabetes mellitus (T2DM) on the basis of determination of markers of endothelial dysfunction. Material and Methods: This was a single-center, prospective cohort longitudinal study with a two-year observation period. Totally, 136 patients with T2DM and DR were included. They were divided into three groups: group 1 of 60 eyes with mild non-proliferative DR (NPDR), group 2 of 42 eyes with preproliferative DR (PPDR), and group 3 of 34 eyes with PDR. Enzyme-linked immunosorbent assay (ELISA) was used to determine serum levels of highly sensitive C-reactive protein (hs-CRP), endothelin (ET)-1, endothelial-monocyte-activating polypeptide II (EMAP II), endothelial nitric oxide synthase (eNOS), interleukin (IL)-1β IL-6, and nitric oxide metabolites (NOx). Repeat ophthalmological examination was performed after two years of treatment which included conservative treatment, laser photocoagulation, anti-vascular endothelial growth factor (VEGF) treatment, surgery (vitrectomy), or their combinations. Results: Baseline blood levels of all endothelial dysfunction markers (with the exception of eNOS) among patients with DR were 1.9–16.4 higher compared to controls (p < 0.001), and gradually increased with the stage of DR. Baseline blood eNOS levels among patients with DR were 1.5–3.7 times lower compared to controls (p < 0.001), and decreased with the stage of DR. Receiver operating characteristic (ROC) curves of the models obtained showed strong associations (area-under-curve (AUC) = 0.77–0.88) of all endothelial dysfunction factors (with the exception of NOx) with the risk of fast DR progression. The univariate models involving EMAP-II, hs-CRP and IL-6 yielded the highest AUC values (> 0.8). Although the specificity of the univariate models involving EMAP-II, hs-CRP, eNOS and IL-6 exceeded 85%, their sensitivity was rather low. The multivariate model for predicting the risk of fast DR progression involved EMAP-II and eNOS, indicating a key role of these markers in determining the efficacy of treatment for DR. The discriminative ability of the model was adequate (AUC = 0.92 (95% CI, 0.86–0.96)), and its sensitivity and specificity were excellent (81.0% and 91.2%, respectively). Conclusion: The association of endothelial dysfunction markers with the outcome of treatment for DR was demonstrated. The model predicting the efficacy of treatment of DR in the Ukrainian population and involving the most significant endothelial dysfunction markers (EMAP-II and eNOS) was for the first time developed.